Analysis of Product Defects in the Packing Production Process at PT.XYZ Using FTA and FMEA Methods - Wulandari, Rina Sri; Hakim, Luqman; Fahmi Haris, Rivandy (Journal Knowledge Industrial Engineering (JKIE), 2022)
A product defect is a product failure that does not meet the quality and standards that have been determined from a product. Product defects occur because of a problem in the production process. With a product defect in the coffee packing production process at PT. XYZ, one of which is unstable weight and the exp date is not printed, so the researcher analyzes the problem with one of the six sigma methods, namely using the FTA and FMEA methods. Failure Tree Analysis (FTA) is a graphical model containing the various parallels and various sample errors that lead to the occurrence of an undesired event. Meanwhile, Failure Mode and Effect Analysis (FMEA) is a structured procedure to identify and prevent possible failure modes. In this study, four types of defects occur in the packaging process including folded packaging, top leaking packaging, bottom leaking packaging, blurry exp date.